The Utilization of Lichen As Biomonitoring NO2 Gas Emission in The City of Palembang - Tri Mardiani; Nazip Khoiron; Meilinda Meilinda (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2024)
AbstractThis study aims to determine the type of lichen as a bioindicator of air pollution and its potential in biomonitoring NO2 gas emissions in the air using the index of atmospheric purity (IAP) calculation method. The research area was divided into 4 sampling stations. One location is a motorised traffic-free area designated as station 1. Station 2, 3, and station 4 are areas located on roads with different motorised traffic densities. At stations 1, 2, 3 and 4, NO2 pollutant levels were measured following the SNI 19–7119.2–2005 procedure with the Griess Saltzman method. Furthermore, at the same station, the pollution level was also determined by calculating the IAP value. Based on the IAP value, the pollution level at the research area station is in the low-very high category with NO2 gas pollution levels in the range of 7.95–12.1 μg/Nm3/hour. There are 8 species of lichen whose presence can serve as bioindicators of NO2 pollution in the air. These species are Graphis sp., Lecanora sp., Lepraria sp., Dirinaria sp., Graphis scripta, Canoparmelia sp., Ochrolechia sp., and Lecidella elaeochroma. The results of the average measurement of NO2 levels show that NO2 levels at the four sampling stations are still in a safe status because they are still below the air quality standards. The IAP value has a negative correlation with NO2 levels in the air, where the higher the NO2 levels in the air, the lower the IAP value, otherwise if the NO2 levels in the air are lower, the IAP value will be higher. The Pearson Correlation test shows that there is a negative relationship (unidirectional relationship) between NO2 levels in the air and IAP values. The higher the pollutants in an area, the lower the number of colonies and area of lichen cover on trees, especially in lichen species that are sensitive to air pollution.AbstrakPenelitian ini bertujuan untuk mengetahui jenis lichen sebagai bioindikator pencemaran udara dan potensinya dalam biomonitoring emisi gas NO2 di udara dengan metode perhitungan index of atmospheric purity (IAP). Area penelitian dibagi menjadi atas 4 stasiun sampling. Satu lokasi merupakan area bebas lintasan kendaraan bermotor yang ditetapkan sebagai stasiun 1. Stasiun 2, 3, dan stasiun 4 yaitu area yang berada pada ruas jalan dengan kepadatan lalu lintas kendaraan bermotor yang berbeda. Pada stasiun 1, 2, 3 dan 4 diukur kadar pencemar NO2 mengikuti prosedur SNI 19–7119.2–2005 dengan metode Griess Saltzman. Selanjutnya, pada stasiun yang sama ditentukan pula tingkat pencemarannya dengan menghitung nilai IAP. Berdasarkan nilai IAP, tingkat pencemaran pada stasiun area penelitian berada pada kategori rendah-sangat tinggi dengan kadar pencemar gas NO2 berada pada kisaran 7,95–12,1 μg/Nm3/jam. Ada 8 jenis lichen yang kehadirannya dapat berfungsi sebagai bioindikator pencemaran NO2 di udara. Jenis tersebut adalah Graphis sp, Lecanora sp., Lepraria sp., Dirinaria sp., Graphis scripta, Canoparmelia sp., Ochrolechia sp., dan Lecidella elaeochroma. Hasil pengukuran rata-rata kadar NO2 menunjukkan bahwa kadar NO2 di empat stasiun pengambilan sampel masih dalam status aman karena masih di bawah baku mutu udara. Nilai IAP memiliki korelasi negatif dengan kadar NO2 di udara, dimana semakin tinggi kadar NO2 di udara, maka nilai IAP akan semakin rendah, sebaliknya jika kadar NO2 di udara semakin rendah, maka nilai IAP akan semakin tinggi. Melalui uji Korelasi Pearson, menunjukkan bahwa terdapat hubungan negatif (hubungan tidak searah) antara kadar NO2 di udara dengan nilai IAP. Semakin tinggi polutan di suatu area, semakin rendah jumlah koloni dan luas penutupan lichen pada pohon, terutama pada jenis lichen yang sensitif terhadap polusi udara.